Efficacies of Ivermectin and Praziquantel Treatment on Intestinal Helminthiases among Primary School Children in Ihiala, Anambra State, Nigeria - Emmy-Egbe , Ify Oslar; Oluchukwu , Onyema Chidimma (African Journal of Education,Science and Technology (AJEST), 2013)
Studies to determine the efficacies of Ivermectin and Praziquantel (anthelmintics) in the treatment of intestinal helminthiasis among primary school children in Ihiala, Ihiala L.G.A were conducted from April to September 2012. Consent was obtained from the Local Government Health Authority and Head of various schools. Direct saline wet mount technique and floatation technique were used to examine the stool samples for helminth parasites. Of the 200 subjects examined, 117 were infected giving a prevalence of 58.5%. The 0-15years examined had different intestinal helminthiases namely; Anclostoma duodenale, Ascaris lumbricoides and Taenia saginata. A total number of 73 (36.5%) were cured using the drugs. Helminth infections in the order of prevalence were; Ascaris lumbricoides (21.5%), Ancylostoma duodenale(16.5%) and Taenia saginata (20.5%). The highest prevalence of 90% was observed in the 13-15 years age group. The males were infected more than the females. The anthelmintic drugs used in the study were effective against the intestinal helminth parasites. The promotion of better environmental conditions and placing greater emphasis on health education with respect to personal hygiene, deworming programme and good eating habits will enhance the control and prevention of common parasitic infections in Ihiala and Nigeria at large.